Análise dos atropelamentos de vertebrados terrestres em unidades de conservação brasileiras à escala da paisagem - Reis, Mardiany Ribeiro dos (2015)
Among its negative impacts on biodiversity, the roadkill of wild animals is being considered one of the most worrying recently. For this reason, it is necessary to understand what are the factors that lead to a greater incidence of roadkill on certain stretches. The characteristics of the landscape and of the road have been considered as factors that may promote the incidence of roadkill. The main objective of this work is to understand the relationship between surrounding landscape and road structures with the occurrence of roadkill of amphibians, reptiles and mammals. We used roadkill data from the years 2013 and 2014 of five brazilian protected areas. They were built generalized linear models mixed to assess the relationship between the occurrence of roadkill with the landscape variables (type of use and land cover) and the presence / absence of transport infrastructure (bridges and drainage pipes). The surrounding landscape was more important for the majority of taxonomic groups: The roadkill of amphibians is positively related to silviculture and negatively with the grassland and agriculture; mortality of reptiles is associated to increase of agriculture and native forest and “small escansoriais” has a negative association with the silviculture. In the group of “semi-fossorial” the presence of bridges was related to the possibility reduction of roadkill and presence of drainage pipes with the increasing. Depending on the target group suggests to adopt measures to reduce the probability of roadkill on the basis of soil use.